ANALISIS PENGARUH PEMBERIAN AROMATERAPI EKSTRAK MAWAR (Rosa Centifolia Extract) DAN EKSTRAK LEMON (Citrus Limon Extract) TERHADAP TEKANAN DARAH WANITA LANSIA DI WILAYAH KERJA PUSKESMAS TIGO BALEH KOTA BUKITTINGGI TAHUN 2021 - Khairul Abbas; Wati Husna (HUMAN CARE JOURNAL, 2021)
AbstractHypertension or increasing blood pressure is a silent killer because it does not have typical symptoms such as headaches, shortness of breath, heart palpitations, easy fatigue, ringing in the ears, nosebleeds, blurred vision caused by damage to the brain, eyes, heart and kidneys. The incidence of hypertension is higher as age increases (elderly). Natural remedies have existed since ancient times. One of them is rose extract aromatherapy and lemon extract which stimulates the thalamus and provides a calming, relaxing effect and it can reduce blood vessel vasoconstriction activity, thereby lowering blood pressure.The type of this research was quantitative with quasi-experimental research design by using pretest and posttest designs with control group. It was conducted in Tigo Baleh Community Health Center Work Area, Bukittinggion May–August 2021 on 60 hypertensive elderly. They had been chosen by purposive sampling technique. The data were analyzed by statistical test with paired test for the intervention group and Wilcoxon test for the control group.The results of this research showed that aromatherapy intervention group of rose and lemon extracts obtained p value = 0.000 (p <0.05) for systole and diastole. It means that there was an aromatherapy effect of rose and lemon extracts on blood pressure. Then, for the control group, p = 0.943 (p>0.05) for systolic and p = 0.796 (p>0.05) for diastolic means that there was no significant difference between systolic and diastolic blood pressure in the morning and evening measurements in the control group.From the research above, it can be concluded that rose and lemon extract aromatherapy has an effect on blood pressure in hypertensive elderly women. It is expected that Community Health Center to implement and provide aromatherapy counseling that can reduce the incidence of hypertension in elderly women in addition to providing hypertension drug therapy.